Building agent-customer relationship in takaful industry: a framework of Islamic relationship marketing - Che Mohd Salleh, Marhanum; Abdullah, Nurdianawati Irwani; Razali, Siti Salwani (International Shari'ah Research Academy for Islamic Finance (ISRA), 2012)
The term ‘relationship marketing’ has grown to become a popular subject in the marketing literature since the last three decades. The literature indicates the significance of maintaining long-term relationship with customers, especially in current days. The questions then arise are: what are the antecedents that significantly contribute in building and maintaining a long-term buyer-seller relationship?; and what are the outcomes of a strong buyer-seller relationship? The discussions on relationship marketing have even gained popularity in the Asian literature since 2000s; yet research conducted on the issue of Malaysian Islamic financial institutions is very scarce. The existence of a gap in the Asian literature on this topic has led the researchers to develop a suitable theoretical framework of Islamic relationship marketing for Islamic financial institutions, particularly the Takaful industry. The study expects that the framework of Islamic relationship marketing will be a material of reference for the Takaful industry players in strengthening their relationship with their customers. Indeed, a strong agent-customer relationship will ensure the development of the Takaful industry in the future.